Physical properties of L-asparaginase from Serratia marcescens. - Stern, M L (1976)
Purified L-asparaginase from Serratia marcescens had an apparent-weight average molecular weight of 171,000 to 180,000 as determined by electrophoresis on polyacrylamide gels and by sedimentation equilibrium at low speed in an analytical ultracentrifuge. A subunit molecular weight of 31,500 +/- 1,500 was estimated for the enzyme after treatment with sodium dodecyl sulfate and urea and electrophoresis on polyacrylamide gels; a similar value was obtained by high-speed sedimentation equilibrium in the presence of guanidine hydrochloride. Our data indicate that the Serratia enzyme could have five or six subunits of 32,000 daltons, compared to four subunits of 32,000 daltons in the Escherichia coli enzyme. The Serratia L-asparaginase also appears to be a larger molecule than the enzyme from Erwinia carotovora, Proteus vulgaris, Acinetobacter glutaminasificans, and Alcaligenes eutrophus. The Serratia enzyme, like that from E. caratovora, was more resistant than the E. coli enzyme to dissociation by sodium dodecyl sulfate. This resistance could be due to the finding that the Serratia enzyme had a relatively high hydrophobicity, similar to the enzyme from E. caratovora, when compared with the hydrophobicity of the E. coli enzyme. The isoelectric point of the Serratia enzyme was approximately 5.2. The influence of certain physical characteristics of the enzyme on the biological properties is discussed.